Forward rate bias in developed and developing countries: More risky not less rational - Michael D. Goldberg; Olesia Kozlova; Deniz Ozabaci (Econometrics, 2020)
This paper examines the stability of the Bilson-Fama regression for a panel of 55 developed and developing countries. We find multiple break points for nearly every country in our panel. Subperiod estimates of the slope coefficient show a negative bias during some time periods and a positive bias during other time periods in nearly every country. The subperiod biases display two key patterns that shed light on the literature's linear regression findings. The results point toward the importance of risk in currency markets. We find that risk is greater for developed country markets. The evidence undercuts the widespread view that currency returns are predictable or that developed country markets are less rational.
Keywords: 330; currency risky; imperfect knowledge; Knightian Uncertainty; structural change